2009
DOI: 10.4104/pcrj.2009.00043
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care centres with asthma clinics: effects on patients' knowledge and asthma control

Abstract: Aim: To evaluate outcomes for patients attending primary care centres with and without asthma clinics. Methods:A cross-sectional survey at 42 primary health care centres randomly selected according to organisation of asthma care, 14 with complete, 14 with incomplete and 14 with no asthma clinic according to national criteria. 1,477 randomly selected patients 15-45 years received two questionnaires. Outcomes were: patients' knowledge of asthma; asthma control; and quality of life.Results: Patients attending pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
1
19
1
1
Order By: Relevance
“…In our study, spirometry, peak flow monitoring or both was performed in almost every planned contact if patient encountered both nurse and GP. This suggests that planned asthma follow-up contact may benefit from the involvement of both professionals 50 . In a Danish study 29 , planned asthma management by both nurse and doctor participating with systematic approach improved asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, spirometry, peak flow monitoring or both was performed in almost every planned contact if patient encountered both nurse and GP. This suggests that planned asthma follow-up contact may benefit from the involvement of both professionals 50 . In a Danish study 29 , planned asthma management by both nurse and doctor participating with systematic approach improved asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses as educators can generate significant reductions in the cost for asthma care, for example through decreased emergency department visits and improved self-management of asthma exacerbations (124). Having access to an asthma nurse in primary care in Sweden and internationally has been shown to increase patient knowledge, improve asthma control and reduce costs (125)(126)(127).…”
Section: Adherence To Guidelines (Studies I Ii Iii and Iv)mentioning
confidence: 99%
“…These findings are not consistent with other reports showing that access to an asthma nurse in primary care improves knowledge about and control of the disease, as well as quality of life. 11,13 In addition, a Dutch study showed that care provided by a specialised asthma nurse is as effective in the outpatient management of stable childhood asthma as traditional management by a paediatrician or GP. 43 Furthermore, attention to clinical guidelines can improve evidence-based nursing practice in connection with the non-pharmacological management necessary for optimal treatment of childhood asthma in which specialised asthma nurses are highly skilled.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…9,10 Factors reported to facilitate asthma control include the use of a spirometer and access to a specialised asthma nurse. 11,12 Having access to an asthma nurse has been shown to increase patients' knowledge, improve asthma care, and reduce costs. 13 In several fields of medicine, many patients fail to achieve the goals set by evidence-based guidelines [14][15][16][17] and, for adults with asthma, adherence to guidelines in primary care has been reported to be poor.…”
Section: Introductionmentioning
confidence: 99%